Operational Risk Management Design Based on The COSO Enterprise Risk Management Approach : Case Study at TMAP - Arya Prabadaru; Yan Rahadian (Yayasan Riset dan Pengembangan Intelektual, 2024)
Every business activity is always filled with uncertainty which can create risks. These risks can have a negative impact on achieving the company's vision, mission and goals. Therefore, handling these risks must be carried out in a comprehensive and integrated manner. Risk management is a system or method for managing, supervising and controlling a company's exposure to risk. This research uses COSO ERM 2017 as a reference for conducting gap analysis and designing a company risk management framework. Apart from that, this research also aims to design a risk management framework according to the COSO ERM 2017 framework. The results of this research show that TMAP has not implemented every risk management principle based on COSO ERM 2017. However, there are several principles that have been implemented by TMAP, namely demonstrating commitment to core values; Attracts, Develops and Retains Capable Individuals; Analyze Business Context, Formulate Business Objectives; Identify Risks. However, these principles have not been implemented completely, but only in part. With this research, it is hoped that it will be able to provide benefits and be useful for the following parties, namely that this research can be input for improving the function and role of risk management in operational activities so that it can increase productivity in accordance with the company's strategy. And academically, this research can be a reference for future research on risk management, especially in companies operating in the chemical trading industry.